A New Species of Lithocarpus (Fagaceae) from Ca Dam Mountain of Quang Ngai Province, Vietnam - Ngoc, Nguyen Van (2023)
Lithocarpus cadamensis Ngoc & Son, a new species of Fagaceae, is described and illustrated from Mt. Ca Dam, Tra Bong District, Quang Ngai Province, central Vietnam. The new species is characterized by its large leaf blades with long petioles, solitary and subsessile cupules which almost completely cover the nut, and spiny cupule scales, in a combination that clearly differs from the previously known species of Lithocarpus including the most similar species in the region, L. campylolepis, L. eucalyptifolius, and L. gougerotae. A MIG-seq phylogeny based on genome-wide SNPs reveals a phylogenetic position close to L. eucalyptifolius, from which the new species is differentiated by multiple morphological characters. A morphological description and comparison with related species, photographs, line drawing, preliminary conservation status, and DNA barcode sequences are provided for the new species.